A Tale of two cities : the economic development of Hong Kong and Singapore. - Luah, Jiun Yih. (2008)
This project examines the economic developments of Hong Kong and Singapore. Both city-states achieved remarkable economic development although the policies adopted by them differ. Specifically, entrepreneurship, government and government policies and labour of each economy are discussed in this report. The differences in the policies adopted by both economies are highlighted.